2020
DOI: 10.5187/jast.2020.62.2.227
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on single- and mixed-strain fermentation of ruminant feeds

Abstract: Use of raw feedstuffs for livestock is limited by low digestibility. Recently, fermentation of feedstuffs has been highlighted as a new way to improve nutrient absorption through the production of organic acids using inoculated microorganisms, which can also play a probiotic role. However, standard procedures for feedstuff fermentation have not been clearly defined because the process is influenced by climatic variation, and an analytical standard for fermented feedstuffs is lacking. This study aimed to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…Similarly, Choi et al [ 25 ] obtained the optimal medium for L. plantarum 200,655 through RSM experiments on carbon and nitrogen sources. The fermentation condition is another key factor to the success of fermentation [ 26 ]. A fermentation time of 36 h, an inoculation amount of 10%, and a ratio of material to water of 1:1 is the optimal fermentation scheme.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Choi et al [ 25 ] obtained the optimal medium for L. plantarum 200,655 through RSM experiments on carbon and nitrogen sources. The fermentation condition is another key factor to the success of fermentation [ 26 ]. A fermentation time of 36 h, an inoculation amount of 10%, and a ratio of material to water of 1:1 is the optimal fermentation scheme.…”
Section: Discussionmentioning
confidence: 99%
“…fungi , which may be due to the interaction between strains. Seungmin et al [ 16 ] have shown that mixed fermentation is a very complex process, and pH and temperature will affect the properties of microorganisms. The decline in enzyme activity in later stages may be attributed to nutrient competition among strains.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a mixed fermentation is commonly used in the processing of some products. Some studies show that mixed fermentation can make up for the deficiency of a single fermentation [ 16 ].…”
Section: Introductionmentioning
confidence: 99%